Wisata Halal Tinjauan Fatwa DSN-MUI Nomor: 108/DSN-MUI/X/2016 Tentang Pedoman Pariwisata Berdasarkan Prinsip Syariah (Studi di Dusun Pancer Desa Sumberagung Kecamatan Pesanggaran Kabupaten Banyuwangi) - Elsa Assari (Journal of Islamic Business Law, 2018)
The development of tourism which is currently becoming a trend in some countries is development of syariah or tourism is often referred to as kosher tours. The development of tourism of Sharia is judged to be an excellent development of tourism on the social, economic and cultural circumstances for a country or region. Concept of halal tourism developed in Banyuwangi Regency Government as differentiation and segmentation of Banyuwangi tourism against other areas. Halal tourism label will be differentiator between tours in Banyuwangi tourism other areas particularly in East Java province The purpose of this research is to know development of Pulau Merah in village of Kecamatan Sumberagung of Banyuwangi, and to know Organization of the Pulau Merah tourism based on sharia principles in accordance with the MUI perspective. This research is classified into types of empirical legal research. The study also called research field research due to more emphasis on the research of data field as object is examined. The approach used is a qualitative approach. In this study data analysis method used is descriptive analysis method.The results showed that 1) Government of Banyuwangi Regency develop products halal on every tourist atractions that exist in other countries especially Pulau Merah. 2) Development of community's role is indispensable in order to run well the concept of halal tourism. Majelis Ulama Indonesia serves as the institution that became a supervisor in the construction development of halal tourism is being encouraged by Government of Banyuwangi Regency